Improving immunization equity through a public-private partnership in Cambodia - J. Brad Schwartz; Indu Bhushan (The World Health Organization, 2004)
OBJECTIVE: To examine the effects on immunization equity of the large-scale contracting of primary health-care services in rural areas of Cambodia. METHODS: Data were obtained pre-intervention and post-intervention from a large-scale quasi-experiment in contracting with nongovernmental organizations to provide primary health care in nine rural districts of Cambodia between 1999 and mid-2001. Coverage targets and equity targets for all primary health-care services, including immunization of children, were explicitly included in the contracts awarded in five of nine rural districts which together have a population of over 1.25 million people. The remaining four districts used the traditional government model for providing services and were given identical targets. FINDINGS: After the 2.5 years of the trial, bivariate and multivariate analyses of the results suggested that although there was a substantial increase in the proportion of children who were fully immunized in all districts, children in the poorest 50% of households in the districts served by contractors were more likely to be fully immunized than poor children living in similar circumstances in districts using the government's model, all other things being equal. CONCLUSION: The contracting approach described in this paper suggests a means of moving towards a more equitable distribution of immunization services in developing countries.